APLIKASI PUPUK DAUN UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL BAWANG DAYAK (Eleutherine palmifolia (L.) Merr) - Elva Suryani; Ronny Yuniar Galingging; Widodo Widodo; Marlin Marlin (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[APPLICATION OF LEAF FERTILIZER TO INCREASE THE GROWTH AND YIELD OF BAWANG DAYAK (Eleutherine palmifolia (L.) Merr)]. Bawang Dayak (Eleutherine palmifolia (L.) Merr) is a potential medicinal plant and required improved growth and yield through the application of appropriate fertilizers. This study aimed to increase the growth and yield of bawang Dayak by determining the optimum concentration and time interval of foliar fertilizer application. The experiment was arranged in a completely randomized block design factorial. The first factor was the concentration of foliar fertilizer, consisting of 0,1, 2, and 3 g/L. The second factor was interval application of foliar fertilizer, consisting of every day, every 3 days, every 6 days, and every 9 days. The results showed that bawang Dayak did not show a significant response to foliar fertilizers. However, there was an interaction between the concentration and interval of foliar fertilizer application which had a significantly different effect on plant height. The highest plant height occurred at intervals of 3-day foliar fertilizer application with a concentration of 3 g/L. The concentration of foliar fertilizer had a significant effect on the variables of plant height, bulb fresh weight, as well as the bulb numbers. All concentrations of foliar fertilizer (0-3 g/L), and time intervals of foliar fertilizer application (1-9 days) affected the same growth and yield response of Bawang Dayak.